Anticipated alternative policy-rate paths in policy simulations - Stefan Laséen; Lars E.O. Svensson (Sveriges Riksbank, 2011)
This paper specifies a new convenient algorithm to construct policy projections conditional on alternative anticipated policy-rate paths in linearized dynamic stochastic general equilibrium (DSGE) models, such as Ramses, the Riksbank's main DSGE model. Such projections with anticipated policy-rate paths correspond to situations where the central bank transparently announces that it, conditional on current information, plans to implement a particular policy-rate path and where this announced plan for the policy rate is believed and then anticipated by the private sector. The main idea of the algorithm is to include among the predetermined variables (the state of the economy) the vector of nonzero means of future shocks to a given policy rule that is required to satisfy the given anticipated policy-rate path.
Keywords: E52; E58; 330; optimal monetary policy; instrument rules; policy rules; optimal policy projections; Geldpolitik; Regelbindung; Dynamisches Gleichgewicht; Theorie